Abp Henryk J. Muszyński, Początek wspólnej drogi. Dialog katolicko-żydowski w Polsce w latach 1986–1994, Gniezno–Pelplin: Bernardinum 2015, 656 s. - Szuppe, Paweł (Studia Nauk Teologicznych PAN, 2020)
Recenzja